Verbal symbolization of Ukrainian culture in business branding strategies - Zbinska , Anna (Current issues of Ukrainian linguistics: theory and practice, 2025)
The article explores the phenomenon of language symbolization of Ukrainian culture in the context of the verbalization of business branding strategies. The author analyzes communicative nature of quotations, allusions, aphorisms, and stylization techniques in their function as markers of national identity within the modern commercial sphere. Oriented toward image-based representationality, axiological significance, and emotional resonance, such precedent-related contexts are presented in the author's argumentation as components of the society's value paradigm. It enables their analysis within the framework of business linguistics from the perspective of temporal and spatial dynamization of Ukrainian culture across different stages of its development.The research focuses on the integration of Ukrainian literary, artistic, and philosophical contexts into contemporary commercial discourse. The article emphasizes the importance of language representation in the creation and reproduction of the national narrative under conditions of globalized media communication. It is determined that modern Ukrainian brands actively incorporate emblematic figures of the national cultural space – such as Taras Shevchenko, Lesya Ukrayinka, Vasyl Stus, and Hryhorii Skovoroda – into the verbal and visual format of business activities, thereby creating a recognizable communicative code that appeals to both verbal and non-verbal cultural values within the social languageconsciousness.Special attention is paid to the communicative strategies through which a brand reflects the symbolic space of culture: language stylization, allusions, reminiscences, and intertextuality. The article examines the business practices of brands such as byMe, Oliz, Marmur, and Orner, which represent the textual component of branding as a full-fledged semiotic resource aimed at deep cultural interpretation and decoding. It is emphasized that language in such projects is not a secondary element in relation to the visual context, but functions as a semantic foundation that shapes the brand's image-building perspective.
Keywords: verbal symbolization; branding; cultural identity; intertextuality; communicative strategy; media communication